Teratogenic Effects of Lixisenatide: Anatomical Malformations and Histopathological Changes in Developing Chick Embryos - Yogesh Yadav; Amit Kumar Srivastava; Ashok Kumar Gupta (Medical Science: Recent Advances and Applications Vol. 4, 2025)
Background: Lixisenatide is a peptide containing 44 amino acids, which is amidated at the C-terminal amino acid. At present Lixisenatide is the drug been used to treat type 2 diabetes mellitus. Therapeutically is been considered to be best for treatment of diabetes mellitus than other GLP1 receptor antagonists. However, there is limited available data about effect of lixisenatide on liver, kidney, stomach and cerebral cortex. Studying the teratogenic effects of lixisenatide is important for human welfare. Objectives: This study aims to find out gross anatomical malformations due to teratogenic effects of antidiabetic drug Lixisenatide on developing chick. Methods: It was an Interventional study conducted at the Department of Anatomy, Santosh Medical College, Ghaziabad, India. It is confirmed from the literature survey/ pilot study that the expected mean ± SD of the parameter of control and experimental groups are 27±5.32 with 32±5.30, with the help of software G* Power analysis for \(α\) 5% and Power (1-\(β\)) 95.36%. The effect size is 1.961, and the sample size for each group is 28. So, we have taken the total sample size of 280. Descriptive statistical analysis, which included frequency and percentages, was used to characterise the data. Inferential statistics included a chi-square test and an independent samples t-test for different dependent variables of the study, and p<0.05 was considered statistically significant. Results: Gross anatomical malformation was seen after administration of lixisenatide as compared to the control group. Histological sections D and Dd (magnified at 10X and 40X, respectively) of the liver treated with a higher dose of lixisenatide on embryonic day 21 show congestion of the central vein accompanied by infiltration of inflammatory cells. The most common anatomical malformation was growth retardation followed by limbs deformity and twisted neck and it was statistically significant (p<0.05) significant decrease in the weights of treated chick embryo compared to the control groups (p<0.05). Conclusion: The findings generated in this study show teratogenic effects like anatomical malformations and histopathological changes due to effects of high dose of Lixisenatide on developing chick embryo in liver organ and these teratogenic effects may be extrapolated to human being.